2015
DOI: 10.1155/2015/101438
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the Orbit in East-European Population Based on Three-Dimensional CT Reconstruction

Abstract: Objectives. To determine safe distances within the orbit outlining reliable operative area on the basis of multislice computed tomography (MSCT) scans.Patients and Methods. MSCT of orbits of 50 Caucasian patients (26 males and 24 females, mean age 56) were analysed. Native scans resolutions were in all cases 0.625 mm. Measurements were done in postprocessing workstation with 2D and 3D reconstructions. The safe distances values were calculated by subtracting three standard deviations from the arithmetical avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…The study of Nitek et al on morphometry of the orbit in an east European population based on three-dimensional CT reconstruction measured the minimal safe distances of 50 Caucasian patients from ALC-AEF, AEF-PEF, and PEF-OC at 27.7 ± 2.8 mm, 10.6 ± 3.3 mm, and 5.4 ± 1 mm, respectively which as compared to our study has a 4 mm difference for ALC-AEF, 0.27 mm difference for AEF-PEF and 1.99 mm difference for PEF-OC. 5 Cankal et al obtained average distances of 13.7 mm and 8.5 mm for the AEC-PEC and PEC-OC respectively in their study of 150 PNS CT scans in Turkey which also differs from our study from which there is a 2.83 mm difference for AEF-PEF and 1.11 mm difference for PEF-OC. 6 Cánovas et al measured 11.24 ± 2.14 mm for the AEF-PEF and 7.26 ± 1.33 mm for the PEF-OC in their study of 20 CT scans of cadaver heads in Spain which also did not match our study with a 0.37 mm difference for AEF-PEF and 0.13 mm difference for PEF-OC.…”
Section: A B Ccontrasting
confidence: 95%
“…The study of Nitek et al on morphometry of the orbit in an east European population based on three-dimensional CT reconstruction measured the minimal safe distances of 50 Caucasian patients from ALC-AEF, AEF-PEF, and PEF-OC at 27.7 ± 2.8 mm, 10.6 ± 3.3 mm, and 5.4 ± 1 mm, respectively which as compared to our study has a 4 mm difference for ALC-AEF, 0.27 mm difference for AEF-PEF and 1.99 mm difference for PEF-OC. 5 Cankal et al obtained average distances of 13.7 mm and 8.5 mm for the AEC-PEC and PEC-OC respectively in their study of 150 PNS CT scans in Turkey which also differs from our study from which there is a 2.83 mm difference for AEF-PEF and 1.11 mm difference for PEF-OC. 6 Cánovas et al measured 11.24 ± 2.14 mm for the AEF-PEF and 7.26 ± 1.33 mm for the PEF-OC in their study of 20 CT scans of cadaver heads in Spain which also did not match our study with a 0.37 mm difference for AEF-PEF and 0.13 mm difference for PEF-OC.…”
Section: A B Ccontrasting
confidence: 95%
“…Regarding sexual dimorphism in orbital anatomy, previous studies have shown statistically significant differences in orbital volume with men having larger orbit volumes [16,47,48,64] as well as in orbital morphology [11,16,56,60,64]. Regarding the shape of the orbital aperture-the coefficient derived from orbital width and height-which has been described as more round in women [64], our study showed no statistically significant sex-based difference even if the orbital aperture showed a slightly larger height/width ratio in women.…”
Section: Plos Onementioning
confidence: 99%
“…In the study of Kumar and Gnanagurudasan (2015) (10), it was reported that this distance was not affected by the body side difference, but it was longer in male than in female. Similarly, in the study of Nitek et al (2009) (1), the medial wall was found to be longer in male than in female, while in the study of Nitek et al (2015) (23) it was stated that this distance was longer on the right than on the left (p<0.05). In the study of Oester Jr et al (2012) (11), it was evaluated in healthy individuals and individuals with vision loss, and it was reported that there was no significant difference between the two groups (p˃0.05).…”
Section: Discussionmentioning
confidence: 78%